Answer:
The solution is ([tex]\frac{7}{12}[/tex] , [tex]\frac{67}{6}[/tex])
Step-by-step explanation:
∵ y = 14x + 3 ⇒ (1)
∵ y = 2x + 10 ⇒ (2)
→ Equate equations (1) and (2) to find x
∵ 14x + 3 = 2x + 10
→ Subtract 2x from both sides
∴ 14x - 2x + 3 = 2x - 2x + 10
∴ 12x + 3 = 10
→ Subtract 3 from both sides
∴ 12x + 3 - 3 = 10 - 3
∴ 12x = 7
→ Divide both sides by 12 to find x
∵ [tex]\frac{12x}{12}[/tex] [tex]\frac{7}{12}[/tex]
∴ x = [tex]\frac{7}{12}[/tex]
→ Substitute the value of x in equation (1) or (2) to find y
∵ y = 2([tex]\frac{7}{12}[/tex]) + 10
∴ y = [tex]\frac{7}{6}[/tex] + 10
∴ y = [tex]\frac{67}{6}[/tex]
∴ The solution is ([tex]\frac{7}{12}[/tex] , [tex]\frac{67}{6}[/tex])